CampusEats: The Student Food Hub - Sumagi, Muhammad Haziq; Hamzah, Mohd Hamdi Irwan (Applied Information Technology And Computer Science, 2026)
CampusEats is a web-based food ordering system developed to enhance the food purchasing experience within campus environments, particularly at KKTM Seri Gading. Traditionally, students and staff face long queues, limited accessibility to food owner information, and inefficient ordering processes. This project addresses these challenges by offering a centralized platform that enables users to browse menus, place orders, and provide feedback conveniently online. The main purpose of CampusEats is to simplify and streamline food ordering for students, food owner, and the campus community. The system was developed using the Software Development Life Cycle (SDLC) methodology and object-oriented programming principles. Laravel was used as the backend framework, incorporating features such as a payment gateway, customer feedback, and management. The result is a dynamic and user-friendly system that reduces waiting times, improves service efficiency, and supports digital transactions. CampusEats demonstrates its potential to significantly improve the overall food ordering experience on campus. In conclusion, this system serves as an effective digital solution to modernize food ordering and strengthen the connection between students and local food vendor.